The effect of intermittent pneumatic compression on deep-vein thrombosis and ventilation-free days in critically ill patients with heart failure - Hasan M. Al-Dorzi; Abdulaziz Al-Dawood; Fahad M. Al-Hameed; Karen E. A. Burns; Sangeeta Mehta; Jesna Jose; Sami Alsolamy; Sheryl Ann I. Abdukahil; Lara Y. Afesh; Mohammed S. Alshahrani; Yasser Mandourah; Ghaleb A. Almekhlafi; et al. (Scientific Reports, 2022)
Abstract There are contradictory data regarding the effect of intermittent pneumatic compression (IPC) on the incidence of deep-vein thrombosis (DVT) and heart failure (HF) decompensation in critically ill patients. This study evaluated the effect of adjunctive use of IPC on the rate of incident DVT and ventilation-free days among critically ill patients with HF. In this pre-specified secondary analysis of the PREVENT trial (N = 2003), we compared the effect of adjunctive IPC added to pharmacologic thromboprophylaxis (IPC group), with pharmacologic thromboprophylaxis alone (control group) in critically ill patients with HF. The presence of HF was determined by the treating teams according to local practices. Patients were stratified according to preserved (≥ 40%) versus reduced (< 40%) left ventricular ejection fraction, and by the New York Heart Association (NYHA) classification. The primary outcome was incident proximal lower-limb DVT, determined with twice weekly venous Doppler ultrasonography. As a co-primary outcome, we evaluated ventilation-free days as a surrogate for clinically important HF decompensation. Among 275 patients with HF, 18 (6.5%) patients had prevalent proximal lower-limb DVT (detected on trial day 1 to 3). Of 257 patients with no prevalent DVT, 11/125 (8.8%) patients in the IPC group developed incident proximal lower-limb DVT compared to 6/132 (4.5%) patients in the control group (relative risk, 1.94; 95% confidence interval, 0.74–5.08, p = 0.17). There was no significant difference in ventilator-free days between the IPC and control groups (median 21 days versus 25 days respectively, p = 0.17). The incidence of DVT with IPC versus control was not different across NYHA classes (p value for interaction = 0.18), nor across patients with reduced and preserved ejection fraction (p value for interaction = 0.15). Ventilator-free days with IPC versus control were also not different across NYHA classes nor across patients with reduced or preserved ejection fraction. In conclsuion, the use of adjunctive IPC compared with control was associated with similar rate of incident proximal lower-limb DVT and ventilator-free days in critically ill patients with HF. Trial registration: The PREVENT trial is registered at ClinicalTrials.gov, ID: NCT02040103 (registered on 3 November 2013, https://clinicaltrials.gov/ct2/show/study/NCT02040103 ) and Current controlled trials, ID: ISRCTN44653506 (registered on 30 October 2013).